Exotic ladybirds for biological control of herbivorous insects – a review. Issue 1 (11th September 2020) - Rondoni, Gabriele; Borges, Isabel; Collatz, Jana; Conti, Eric; Costamagna, Alejandro C.; Dumont, François; Evans, Edward W.; Grez, Audrey A.; Howe, Andy G.; Lucas, Eric; Maisonhaute, Julie‐Éléonore; Onofre Soares, António; et al.
Abstract: Since the late 19th century, exotic ladybirds (Coleoptera: Coccinellidae) have been used extensively for suppressing herbivorous insects of economic importance. In recent decades, the introduction of non‐native biological control (BC) agents has been greatly limited due to the awareness of the potential non‐target effects of introductions. Nonetheless, recent episodes of biological invasions of economically important pests have raised the need to carefully consider whether the expected benefits of pest control go beyond the possible environmental risks of introduction. To better understand the factors that contributed to successful BC programs, here we review the literature behind classical and augmentative BC using exotic ladybirds. Additionally, by means of case studies, we discuss the BC efficacy of selected exotic species, e.g., Coccinella septempunctata L., Harmonia axyridis (Pallas), and Hippodamia variegata (Goeze), and their position within the communities of predators in the introduced areas of USA, Canada, and Chile. In Europe, much of the research on exotic ladybirds has been conducted on the undesired impact of H. axyridis . Therefore, we summarize the risk assessment data for this species and review the field research investigating the ecological impact on European aphidophagous predators. According to the BIOCAT database of classical BC programs, 212 ladybird species belonging to 68 genera have been released in about 130 years of BC activity, with 14.6% of introductions having resulted in partial, substantial, or complete control of the target pest. However, because post‐release evaluation of establishment and BC success has not always been conducted, this rate could underestimate the successful cases. Among other factors, ladybird establishment and pest suppression mostly depend on (1) intrinsic factors, i.e., high voracity, synchronized predator‐prey life cycle, and high dispersal ability, and (2) extrinsic factors, i.e., adaptability to the new environment and landscape composition. This review contributes to improved understanding of ladybirds as exotic BC agents. Abstract : We analyse and review the current version of the BIOCAT database (CABI) for cases where fully identified exotic ladybird species (Coleoptera: Coccinellidae) were released for classical biological control of herbivorous insects. We discuss the factors promoting ladybird success and non‐target risks of releases by means of case studies relevant for the USA, Canada, Chile, and Europe. Ladybird establishment and pest suppression mostly depend on intrinsic and extrinsic factors. This review contributes to improved understanding of ladybirds as exotic biocontrol agents.